A body in dissonance: young woemn naviagting mental health and living with depression in Cape Town - Oosthuizen, Simone (Social Anthropology, 2022)
This dissertation investigates the experiences of young womxn diagnosed and living with depression in Cape Town. The investigation focuses on the relationship between the young womxn and their bodies as they live with depression and move through depressive episodes. The ethnographic findings expand on the dissociative - depersonalization and derealizationsymptoms of depression. Secondly, the investigation focuses on problematizing the theoretical construct of the body. These young womxn experienced their bodies beyond subject/object, internal/external, body/mind dichotomies. The dissertation frames the ethnographic findings with a phenomenological lens. Additionally, the dissertation uses a sensory gaze to understand the young womxn's bodily experiences and experiences with depression.